Experimental Study of Solvent Debinding on Water Soluble PEG Behavior for Water Atomised SS 316L Compact - Nur Syawanie, Manam; Wan Sharuzi, Wan Harun; Mohd Halim Irwan, Ibrahim (Universiti Malaysia Pahang, 2016)
Growth of environmental friendly binders like Polyethylene glycol (PEG) has received considerable interest because it is a water-soluble binder which is safe to the environment. From the study, PEG removal in water during solvent debinding was observed as a function of temperature against time by determining the density value of compacts. SS 316L water atomised powder around 5 µm particle size with powder loading 61 vol. % were mixed using 73 vol. % of PEG, 25 vol.% of PMMA and 2 vol. % of SA. The injected compact using injection moulding machine was solvent debinding in water leaching at different times and temperatures. The effect of temperature and time on the leaching performance of PEG in water was investigated through relative density observations and microstructural analysis using an optical microscope (OM). The amount of PEG removed increased with time for all temperatures. Observations using different immersion temperatures: 40, 50, 60, 70 and 80 °C with different immersion times were used: 2, 4, 6, 8, and 12 hours (h) for removing the PEG binder. After 12 h, the brown compact at the highest immersion temperature of 80 ºC showed 100 % PEG loss. The microstructure showed that as the time of debinding increased, the shape of the pores and particles became clearer with the remaining binder component of PMMA polymer attached to the particles as most of the PEG was removed from the green compact. The relative density values of the brown compact were reduced when compared to the green compact which ascertained the removal of the PEG binder during the solvent debinding process.